2001
DOI: 10.1046/j.1365-2354.2001.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the effect of progressive muscle relaxation training of patients after stoma surgery

Abstract: Eighteen patients who had undergone stoma surgery were assessed with respect to their anxiety level and self-reported quality of life (QoL) on three occasions; namely, immediately after surgery, 5 weeks after surgery, and 10 weeks after surgery. The patients were randomised into a control group (n = 10) and an experimental group (n = 8). A 20-min set of audiotaped instructions on progressive muscle relaxation training (PMRT) was given to the patients in the experimental group for home practice. Assessment inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Meanwhile, progressive muscle relaxation showed promise as a stress and/or anxiety reduction strategy when used in a group of nursing students in simulation 18. This finding is in agreement with other study results that show a reduction in anxiety after progressive muscle relaxation intervention in different patient populations 33 34. Further studies are needed to look into the effectiveness of these strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, progressive muscle relaxation showed promise as a stress and/or anxiety reduction strategy when used in a group of nursing students in simulation 18. This finding is in agreement with other study results that show a reduction in anxiety after progressive muscle relaxation intervention in different patient populations 33 34. Further studies are needed to look into the effectiveness of these strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Six studies involved alternative medical systems [18][19][20][21][22][23], 14 involved mind body interventions [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], 15 dealt with biologically based therapies [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], seven involved manipulative and body-based methods [54][55][56][57][58][59][60], and two energy therapies [61,62]. A large number of scrutinized studies (overall 495) were not included in the final selection as they were not randomized, did not use a PRO measure or the intervention was not among the list of CAM to be included.…”
Section: Resultsmentioning
confidence: 99%
“…Studies carried out in different fields (stoma patients, patients receiving chemotherapy, dialysis and psychiatric patients, etc) have proved progressive relaxation exercises to be effective in reducing anxiety (9,(16)(17)(18)(19)(20)(21)(38)(39)(40)(41)(42)(43). Dehdari et al (44) applied to patients after CABG surgery studies of state and permanent PMR by reducing levels of anxiety reported that improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…From this research until today, it was found that nursing researcher used PMR in some chronic disease processes, preventing side effects of chemotherapy and dialysis, decrease the pain of patients on surgery and reduce the anxiety level of psychiatry patients, cardiac rehabilitation patients and university students (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%